EXPERIMENTAL RESEARCH OF THE VENTILATION SYSTEM CLEAN AIR INJECTION - YAROPUD, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Microclimate is determined by the combination of temperature, relative humidity, chemical and mechanical composition of the air. Each of the listed indicators separately has a significant impact on the productivity of animals and must be maintained within strict limits determined by the physiological needs and capabilities of animals.In animal husbandry, microclimate is primarily understood as the climate of premises for animals, which is defined as a combination of the physical state of the air environment, its gas, microbial and dust pollution, taking into account the condition of the building itself and technological equipment. In other words, microclimate is the meteorological regime of closed premises for animals, the concept of which includes temperature, humidity, chemical composition and speed of air movement, dustiness, lighting. An optimal microclimate contributes to increasing animal productivity, reducing feed costs per unit of production, and has a positive effect on the preservation of animal health. The microclimate in the premises depends on the local (zonal) climate and the season, the thermal and moisture resistance of the building enclosures, the state of ventilation, the degree of lighting and heating of the premises, the state of the sewage system and the quality of manure removal, the technology of keeping animals, their species and age composition.According to the results of experimental studies of the ventilation system of injection of clean air, it was established that the coefficient of variation of the air speed is lower for the variable width of the gap of the injection nozzle (0.01–0.02), which confirms the validity of theoretical studies.According to the results of the calculation of experimental data, the dependence of the consumed power N of the clean air injection system, which is implemented in production conditions, on the air consumption was obtained. Comparing the results of experimental studies with the results of theoretical calculations, it is clearly visible that the theoretical data are within the margin of error. According to the correlation coefficient of 0.94, the results of theoretical calculations are adequate and can be used in the engineering calculation method.
Keywords: microclimate; temperature; humidity; animal husbandry; ventilation; air; injection; equipment; energy efficiency